Performance analysis of Zigbee WDSN using clustering protocol and STR algorithm - Brigitta, R. Maria; Samundiswary, P. (2017 International Conference on Computer, Communication and Signal Processing (ICCCSP), 2017)
In recent years, wireless networking plays a prominent role because of its easy installation and flexibility. Among the various wireless domains, Zigbee based Wireless Dynamic Sensor Networks (WDSN) pose a good support to the dynamics that arise when the nodes are induced with mobility. In the Zigbee based Wireless Dynamic Sensor Network (WDSN), major consideration is on utilizing the energy efficiently among the mobile nodes. Various techniques are used to attain energy efficiency in Zigbee WDSN. Among them, clustering the nodes is one of the best methods, since they aim at reducing the energy dissipation and increasing the life span of the network. Hence, in this paper, the performance of Zigbee WDSN using clustering scheme is done by considering the nodes with mobility and compared with performance of Zigbee WDSN using non clustering technique. The proposed work is summarized as follows: the network is deployed as clusters and the remaining energy of the node is determined by utilizing clustering protocol. In each cluster, the clustering protocol opts for the node with the maximum remaining energy as the head of that cluster. Then STR algorithm is utilized to route the sensed data from the member nodes to the cluster head. Hence, the clustering technique and STR, route the information through the shortest path paving the way for enhanced average residual energy and Packet Delivery Ratio (PDR). The simulations are done by using ns2 and performance metrics such as average residual energy and PDR are computed and analyzed for non clustered and clustered method.